Role of proinflammatory cytokines in Hashimoto's thyroiditis associated with psychiatric disorders - P. A. Sobolevskaia; A. N. Gvozdeckii; I. V. Kudryavtsev; V. A. Chereshnev; L. P. Сhurilov (Медицинская иммунология)
Mental disorders often accompany autoimmune diseases, for example, since 1949 it has been known about “myxedematous madness”, a psychosis caused by hypothyroidism. The most common cause of hypothyroidism is Hashimoto's autoimmune thyroiditis. It is also known about another neuropsychiatric disorder associated with autoimmune thyroiditis, Hashimoto's encephalopathy. It is a severe dysfunction of the central nervous system, the pathogenesis of which is not associated with hormonal disorders. Cytokines are regulators and participants of inflammation, including autoimmune. Certainly, when we are talking about high concentrations cytokines, we mean systemic inflammation. The minimal or mediocre fluctuations in cytokines within the ranges that are characteristic of healthy status or normergic acute phase response in disease cannot be interpreted from the point of view of binary endocrinological logic. In the CNS, cytokines are able to influence on the neuroendocrine control of systemically regulated functions. It is also important that glial cells (astroglia, microglia) are capable of producing a number of cytokines and can affect neurons and develop behavioral changes. In addition, the ability of a number of cytokines outside the CNS itself to act on vagal afferents and through them to convey information to the CNS, affecting its state and functions, has been proven. It is reasonable to assume that minimal fluctuations in cytokine levels may also affect the state and function of the CNS. The aim of the study was to investigate the levels of cytokines in patients with thyroiditis; in patients with thyroiditis associated with mental disorders; in a group of healthy individuals; and evaluate the effect of cytokine levels on clinical manifestations. In the group of patients with thyroiditis and mental disorders, the levels of CCL20/MIP3α, IL-13, IL-2, IL-27, IL-5 were significantly higher than in other groups. At the same time, no positive correlation was found between the clinical manifestations of mental disorders and the levels of cytokines. A positive correlation was found between the levels of some cytokines and free triiodothyronine, as well as the level of antithyroid antibodies. Mental disorders associated with autoimmune thyroiditis may be associated with changes in the cytokine profile and result from neuroinflammation.